Green Lean TQM Islamic Process Management Practices In Malaysian Food Companies / Nur Asiah Kuzaiman...[et al.] - Kuzaiman, Nur Asiah; Zainuddin, Argustina; Mohd Salleh, Noor Azlina; Kasolang, Salmiah; Abd Rashid, Amirul (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Halal market is expanding globally. With the world Muslim population is approaching 2.8 billion people, Muslims are expected to account for 30% of the world's population by 2025. This large market has created interest from food producing countries worldwide including Malaysia. Being recognized internationally as a progressive Muslim country, Malaysia has the edge of becoming a major producer of Halal food products. Nevertheless, in order to realize this potential demand, the food-based Halal industries should consistently enhance their products by practising a high quality process management system. Lean TQM Islamic Process Management System is a system whereby Process Management Practices are integrated to Lean Manufacturing (LM), Total Quality Management (TQM), Environmental Management System (EMS) and Islamic Manufacturing Practices (IMP) principles. In this study, 30 food companies from Selangor have been selected to participate in this survey. From the data collected, Green Lean TQM Islamic Process framework have been proposed. The implementation practices were divided into 5 categories which are Foundation Level, Level 1, Level 2, Level 3 and level 4. From the data collected in this study, unfortunately there are none of the practices listed in the Foundation levelThe output from this study will provide insights on the good management benchmark that will be beneficial to the food industries, especially for Small and Medium Enterprise (SMEs).